2020
DOI: 10.1111/jam.14898
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐8 gene expression and apoptosis induced by Salmonella Typhimurium in the presence of Bacillus probiotics in the epithelial cell

Abstract: Aims This study aimed to evaluate the effects of three Bacillus probiotics on Salmonella Typhimurium, and interleukin‐8 (IL‐8) gene expression in the co‐culture of the Bacillus and the pathogen in vitro. Methods and Results Bacillus subtilis, Bacillus indicus and Bacillus coagulans were initially turned to spore and heat‐inactivated forms. The cellular damages of the probiotics on the HT‐29 cells were investigated individually and in combination with S. Typhimurium using 3‐(4,5 dimethylthiazol‐2‐yl)‐2,5‐diphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Additionally, B. subtilis produces a variety of digestive enzymes, antimicrobial peptides and other biological active molecules, improving the growth performance of broilers and feed efficiency when supplemented in diets ( Manhar et al., 2016 ; Ramlucken et al., 2019 ; Akhtar et al., 2021 ; Algburi et al., 2021 ; Popov et al., 2021 ). Moreover, B. subtilis is beneficial to the host health through modulation of microbiota composition and humoral immune responses ( Khan and Chousalkar, 2020 ; Kawarizadeh et al., 2021 ). Recently, several clinical and animal trials have demonstrated the protection of B. subtilis against Salmonella and other enteropathogenic bacteria in broilers through the load reduction in intestinal tracts, improvement of the growth performance, and immune responses ( Wu et al., 2018 ; Sokale et al., 2019 ; Abudabos et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, B. subtilis produces a variety of digestive enzymes, antimicrobial peptides and other biological active molecules, improving the growth performance of broilers and feed efficiency when supplemented in diets ( Manhar et al., 2016 ; Ramlucken et al., 2019 ; Akhtar et al., 2021 ; Algburi et al., 2021 ; Popov et al., 2021 ). Moreover, B. subtilis is beneficial to the host health through modulation of microbiota composition and humoral immune responses ( Khan and Chousalkar, 2020 ; Kawarizadeh et al., 2021 ). Recently, several clinical and animal trials have demonstrated the protection of B. subtilis against Salmonella and other enteropathogenic bacteria in broilers through the load reduction in intestinal tracts, improvement of the growth performance, and immune responses ( Wu et al., 2018 ; Sokale et al., 2019 ; Abudabos et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, probiotics have been found to have an inhibitory effect on S. Typhimurium. Bacillus probiotics can inhibit the activity of S. Typhimurium [ 30 ]. Bifidobacterium can down-regulate the gene expression of S. Typhimurium pathogenicity islands 1 and 2 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that heat-inactivated cell-free supernatant (CFS) of selected probiotics reduces the cytotoxicity of S. Typhimurium and inhibits its growth by approximately 50%. Moreover, the expression of the IL-8 gene initially induced by Salmonella was also reduced ( Kawarizadeh et al, 2020 ).…”
Section: Growth Media and Anaerobic Culture Systemsmentioning
confidence: 99%